(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to reveal the impact of using some of the smartphone and tablet applications by ninth grade students on the acquisition of religious concepts in Prophetic Hadith lessons in the Directorate of Education of Marka District in the academic year 2021/2022. To achive the goals of the study, the esearcher used the quasi-experimental method where there were an experimental group and a control group. The study sample consisted of (170) studentst. The researcher prepared the test of religious concepts and verified its validity and reliability, and he uses a software package that contains several programs compatible with the scientific content. The arithmetic means and the standard deviation of the test questions were extracted through using the biserial correlation coefficient and ANCOVA test to examine the outcome’s differences between the two above-mentioned groups. One of the most important results of the study is that there are statistically significant differences between the mean scores of students in the experimental and control groups on the post-religious concepts test attributable to the method used (i.e. smartphone and tablet applications). The study’s recommends incorporating Islamic education curricula with lessons and activities that employ smartphone and tablet applications in the educational process.